COMMUNITY SERVICE THROUGH EMPOWERING KELULUT HONEY IN THE KELULUT MELAKA VILLAGE COMMUNITY - Sirajuddin Sirajuddin; Sahrul Gunawan; Mahyuddin Mahyuddin; Saeed Fayzul Hayat; Ali Mu’min (Yayasan Nuraini Ibrahim Mandiri, 2024)
This community service program aims to improve community empowerment through the cultivation of stingless bee honey in Melaka by involving housewives and local farmer groups as the main targets. The methods used include education on the benefits and techniques of stingless bee cultivation, practical training in making and maintaining nests, and digital-based marketing strategies to increase product competitiveness in the market. Through ongoing mentoring, participants gain a better understanding of business management and marketing of stingless bee products through social media and e-commerce platforms. The evaluation results show an increase in community skills in cultivating stingless bees independently, while opening up new sustainable economic opportunities. Thus, this program not only increases public awareness of the potential of stingless bee honey as an alternative source of income, but also encourages more sustainable and productive management of natural resources.